2005
DOI: 10.1111/j.1365-2621.2005.tb09990.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Processing on the Texture Profile of Canned and Retort Pouch Packed Oil Sardine (Sardinella longiceps) in Oil Medium

Abstract: : Sardine in oil was canned at 3 different Lethality values (F0 5,7, and 9) in retort pouches and aluminum cans in stationary retort. Process time calculations were done mathematically to find out the actual process time. Sardine in oil processed in retort pouches had a lower process time compared with aluminum cans for each F0 value. Instrumental texture analysis was done using a food texture analyzer to study the effect of thermal processing on the texture of thermally processed sardine in oil in aluminum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…Six samples from three pouches were used for the analysis. The texture measurement included 2 consecutive 40 % compressions of the sample at a crosshead speed of 12 mm/min (Bourne 1978;Durance and Collins 1991;Ali et al 2005b). Force by time data from each test was used to calculate mean values for the TPA parameters as described by Bourne (1978).…”
Section: Instrumental Analysis Of Texturementioning
confidence: 99%
See 1 more Smart Citation
“…Six samples from three pouches were used for the analysis. The texture measurement included 2 consecutive 40 % compressions of the sample at a crosshead speed of 12 mm/min (Bourne 1978;Durance and Collins 1991;Ali et al 2005b). Force by time data from each test was used to calculate mean values for the TPA parameters as described by Bourne (1978).…”
Section: Instrumental Analysis Of Texturementioning
confidence: 99%
“…The texture profile analysis (TPA), which measures the compression force of a probe and the related textural parameters of a test food during 2 cycles of deformation of various foodstuffs including fruits, vegetables, bakery, meat products, seafood and specifically retorted products, has been reported (Panifield and Campbell 1990;Durance and Collins 1991;Sanchez-Brambila et al 2002;Caine et al 2003). Ali et al (2005b) showed an improved texture of canned sardine in oil in pouches compared to cans. Texture has been defined as "the sensory and functional manifestation of the structural, mechanical and surface properties of foods detected through the sense of vision, hearing, touch and kinaesthetic" (Szczesniak 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of retort pouch pack in comparison with other thermal processing pack is the shorter cooking time because of its high ration of surface area to volume, so that it has better taste, improved nutritional value and less moisture loss (Trevino, 2009). Retort packaging was commonly used for packaging of various kinds of seafood products, such as sardines (Ali et al, 2005), tuna (Ali et al, 2006), fowl meat (Lyon and Klose, 1981), shrimp (Mohan et al, 2006) but there is only few study on meat products, for instance vegetables with bacon (Heidelbaugh and Karel, 1970) and beef stew (Cremer and Pizzimenti, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…It could be an indication that hardened texture of meat after smoking may considerably get softened with an increase in thermal process. Ali et al, (2005) observed a softening of retort pouch processed sardine meat upon thermal processing to higher F 0 values.…”
Section: Effect Of Thermal Processing On Physicochemical Properties Omentioning
confidence: 83%